THE INFLUENCE OF USING VISUAL PICTURE SEQUENCE TOWARDS STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT - Nurlely, Ledy; Evenddy, Sutrisno Sadji; Arlini, Arlini (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Abstract: This research is aimed to find out whether there is a significant influence of using Visual Picture Sequence towards students’ ability in writing procedure text. This research used quantitative method and quasi experimental design, conducted by using pre-test – treatment - post test design. The instrument used in this research was test (pre-test and post-test). This research was conducted in two classes; experimental class and control class, exactly in English classroom. The population of this research was the twelfth grade of MAN 2 KOTA SERANG in academic year 2020/2021. The samples of this research were XII IPS 2 as experimental class and XII IPS 3 as control class both consisted 33 students. The experimental class was taught by using Visual Picture Sequence and the control class without using Visual Picture Sequence. The data of this research was collected by giving the writing test about procedure text in pre-test and post-test. The post test mean score of control class was 79,75 and the post-test mean score of experimental class was 84,75. The collected data were analyzed by using t-test. The result of data analysis showed that the value of t-count was higher than the value of t-table (11,2 ≥ 2.00) at the level of significant of a 0.05 and degree of freedom is 64. It means that the alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. From those findings, it could be concluded that there was significant influence of using Visual Picture Sequence towards students’ ability in writing procedure text. Keywords: Procedure Text;Visual Picture Sequence; Writing Skill   Abstrak: Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh signifikan dari penggunaan Visual Picture Sequence terhadap kemampuan siswa dalam menulis teks prosedur. Penelitian ini menggunakan metode kuantitatif dengan desain kuasi eksperimen, yang dilakukan dengan menggunakan desain pre test - treatment - post test. Instrumen yang digunakan dalam penelitian ini adalah tes (pre-test dan post-test). Penelitian ini dilakukan di dua kelas; kelas eksperimen dan kelas kontrol, tepatnya di kelas bahasa Inggris. Populasi penelitian ini merupakan kelas XII MAN 2 KOTA SERANG tahun akademik 2020/2021. Sampel penelitian ini adalah XII IPS 2 sebagai kelas eksperimen dan XII IPS 3 sebagai kelas kontrol. Keduanya terdiri dari 33 siswa. Kelas eksperimen diajarkan dengan menggunakan Visual Picture Sequence dan kelas kontrol tanpa menggunakan Visual Picture Sequence. Data penelitian ini dikumpulkan dengan mengadakan tes tulis tentang teks prosedur dalam pre-test dan post-test.  Skor post-test kelas kontrol adalah 79,75 dan skor rata-rata post-test kelas eksperimen adalah 84,75. Data yang dikumpulkan, dianalisis dengan menggunakan t-test. Hasil analisis data menunjukkan bahwa nilai t-count lebih tinggi dari nilai t-table (11.2 ≥ 2,00) pada tingkat signifikan dari 0,05 dan tingkat kebebasan adalah 64. Ini berarti bahwa hipotesis alternatif (Ha) diterima dan hipotesis null (H0) ditolak. Dari temuan tersebut, dapat disimpulkan bahwa ada pengaruh signifikan dari penggunaan Visual Picture Sequence terhadap kemampuan siswa dalam menulis teks prosedur. Kata Kunci: Teks prosedur, visual picture sequence, keterampilan menulis